Motivasi Peternak Ayam Broiler Berbasis Kemitraan Di Kecamatan Kambu Dan Kecamatan Poasia Kota Kendari. - Muhammad Azhar saleh; Musram Abadi; La Ode Arsad Sani (Fakultas Peternakan Universitas Halu Oleo, 2023)
This study aims to analyze the business profile of broiler partnerships in Poasia and Kambu sub-districts and to determine the motivation of plasma broiler breeders to partner with core breeders in Poasia sub-district and Kambu sub-district. This study uses two sources of data, namely primary data and secondary data. Methods of data collection in this study using interviews, observation, and documentation. The research variables include the characteristics of respondents and management of business scale broiler chickens and the level of motivation of farmers in raising broiler chickens. Based on the results of this study, it showed that there were 14 broiler breeders in Kambu District and Poasia District and had different ages, namely 21-55 years. Farmers are categorized as productive age, namely at the age of 46-55 years and in the non-productive age category >55 with a percentage of 21.42%, 3 people. Farmers with high school education level (64.28%). Experience of breeders between 6-10 years with a percentage of 57.14% (8 people), >10 years. The motivation that greatly influences and encourages farmers in partnership-based broiler farming activities in Kambu and Poasia Districts, Kendari City is marketing motivation (68.91%).